Leveraging Brand Extension and Service Innovation in The Digital Era: Transformative Strategies for Medical Scheme - Willie, Michael (Indonesian Marketing Journal, 2025)
Healthcare faces significant digital transformation, urging medical schemes to innovate for competitiveness and member satisfaction. This study investigates how brand extension and service innovation can enhance the competitiveness and sustainability of medical schemes, focusing on differentiation and value delivery. Driven by digital transformation and consumer demands, medical schemes must adopt innovative strategies to effectively meet evolving healthcare needs. This study uses qualitative methods, including literature review and case study analysis, to examine brand extension and service innovation in healthcare. Using data from various medical schemes, a longitudinal analysis conducted from 2015 to 2022 on adopting Efficiency Discount Options (EDOs) versus non-EDO options. It also included a comparative cost analysis and case studies to assess the impact of digital transformation. Of the ten medical schemes analyzed over the period 2016-2022, EDOs grew significantly from 9% in 2016 to 31% in 2022, providing substantial cost savings compared to non-EDO options across the analyzed medical schemes. Additionally, digital transformation in healthcare saw increased adoption of digital platforms, enhancing patient engagement and service delivery, though ethical considerations in telemedicine practices remain crucial. Brand extension and service innovation strategies can enhance member satisfaction and operational efficiency, helping medical schemes differentiate and thrive. This study provides a strategic framework for medical schemes to leverage digital advancements effectively, meet consumer expectations, and achieve sustainable growth in healthcare delivery